ANALISIS EFEKTIVITAS PENGENDALIAN INTERN PERSEDIAAN BARANG DAGANGAN PADA PT. KIMIA FARMA APOTEK 74 MANADO - Tontoli, Sitti Amanah; Elim, Inggriani; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
At a trading company, inventory is an important resource for the survival of the company because in addition to an asset whose value is greater than other current assets is also due to the main source of revenue comes from the sale of inventory. Therefore, effective internal controls are needed to manage the inventory to avoid errors and irregularities. The company is engaged in the pharmaceutical retail sector to manage existing company pharmacies in an effort to increase sales contribution, so that management of inventory management becomes important. The purpose of this study is to determine whether the internal control of merchandise inventory has been effective. The object of this research is PT. Kimia Farma 74 Manado. This research uses descriptiveÂ  qualitative The results showed that the internal control of inventory at PT. Kimia Farma Apotek has been effective in applying pharmacy management management, which can be seen in the implementation of the elements of adequate internal control, good control of the inventory. However, there are still weaknesses in the form of duplicate duties on the function of receipt and storage of merchandise inventory and cash, as well as internal auditor functions captured by the accounting and finance.